Retinal degeneration depends on Bmi1 function and reactivation of cell cycle proteins - Zencak, Dusan; Schouwey, Karine; Chen, Danian; Ekström, Per; Tanger, Ellen; Bremner, Rod; van Lohuizen, Maarten; Arsenijevic, Yvan (Proceedings of the National Academy of Sciences - PNAS, 2013)
The epigenetic regulator Bmi1 controls proliferation in many organs. Reexpression of cell cycle proteins such as cyclin-dependent kinases (CDKs) is a hallmark of neuronal apoptosis in neurodegenerative diseases. Here we address the potential role of Bmi1 as a key regulator of cell cycle proteins during neuronal apoptosis. We show that several cell cycle proteins are expressed in different models of retinal degeneration and required in the Rd1 photoreceptor death process. Deleting E2f1, a downstream target of CDKs, provided temporary protection in Rd1 mice. Most importantly, genetic ablation of Bmi1 provided extensive photoreceptor survival and improvement of retinal function in Rd1 mice, mediated by a decrease in cell cycle markers and regulators independent of p16(Ink4a) and p19(Arf). These data reveal that Bmi1 controls the cell cycle-related death process, highlighting this pathway as a promising therapeutic target for neuroprotection in retinal dystrophies.